Management and outcomes of esophageal perforation. Issue 1 (2nd July 2021) - Axtell, Andrea L; Gaissert, Henning A; Morse, Christopher R; Premkumar, Akash; Schumacher, Lana; Muniappan, Ashok; Ott, Harald; Allan, James S; Lanuti, Michael; Mathisen, Douglas J; Wright, Cameron D
Summary: Background: Esophageal perforation is a morbid condition and remains a therapeutic challenge. We report the outcomes of a large institutional experience with esophageal perforation and identify risk factors for morbidity and mortality. Methods: A retrospective analysis was conducted on 142 patients who presented with a thoracic or gastroesophageal junction esophageal perforation from 1995 to 2020. Baseline characteristics, operative or interventional strategies, and outcomes were analyzed by etiology of the perforation and management approach. Multivariable cox and logistic regression models were constructed to identify predictors of mortality and morbidity. Results: Overall, 109 (77%) patients underwent operative intervention, including 80 primary reinforced repairs and 21 esophagectomies and 33 (23%) underwent esophageal stenting. Stenting was more common in iatrogenic (27%) and malignant (64%) perforations. Patients who presented with a postemetic or iatrogenic perforation had similar 90-day mortality (16% and 16%) and composite morbidity (51% and 45%), whereas patients who presented with a malignant perforation had a 45% 90-day mortality and 45% composite morbidity. Risk factors for mortality included age >65 years (hazard ratio [HR] 1.89 [1.02–3.26], P = 0.044) and a malignant perforation (HR 4.80 [1.31–17.48], P = 0.017). Risk factors for composite morbidity included pleural contamination (odds ratio [OR] 2.06 [1.39–4.43], P = 0.046) and sepsis (OR 3.26 [1.44–7.36], P = 0.005). Of the 33 patients who underwent stent placement, 67% were successfully managed with stenting alone and 30% required stent repositioning. Conclusions: Risk factors for morbidity and mortality after esophageal perforation include advanced age, pleural contamination, septic physiology, and malignant perforation. Primary reinforced repair remains a reasonable strategy for patients with an esophageal perforation from a benign etiology.